PELAKSANAAN MEDIASI DALAM PENANGANAN CERAI GUGAT DI PENGADILAN AGAMA TELUK KUANTAN (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Divorce is a legal and social phenomenon that has a significant impact on family Divorce is a legal and social phenomenon that has a significant impact on family integrity and the psychological stability of the parties involved, particularly women and children. One of the mandatory efforts in resolving divorce cases in court is mediation, as regulated in Supreme Court Regulation Number 1 of 2016 concerning Mediation Procedures in Court. Mediation aims to encourage reconciliation between husband and wife before the examination of the main case proceeds. In practice, the implementation of mediation in divorce lawsuit cases (cerai gugat) at the Religious Court of Teluk Kuantan still faces various obstacles, resulting in a relatively low mediation success rate. The issues examined in this study are: (1) How is the implementation of mediation stages in divorce lawsuit cases at the Religious Court of Teluk Kuantan based on Supreme Court Regulation Number 1 of 2016? (2) What factors and obstacles cause the failure of mediation in divorce lawsuit cases at the Religious Court of Teluk Kuantan? This study aims to determine the implementation of mediation stages in divorce lawsuit cases at the Religious Court of Teluk Kuantan and to identify the factors that contribute to unsuccessful mediation. This research applies an empirical or sociological legal research method, which focuses on the application of law in society. The study is descriptive in nature, aiming to clearly describe the mediation process in handling divorce lawsuit cases. Primary data were obtained through interviews with the Head of the Religious Court, judge mediators, non-judge mediators, community leaders, and parties involved in divorce lawsuit cases. Secondary data were collected from laws and regulations, literature, scientific journals, legal doctrines, and relevant previous studies. The findings show that the implementation of mediation in divorce lawsuit cases at the Religious Court of Teluk Kuantan has generally been carried out in accordance with Supreme Court Regulation Number 1 of 2016, starting from the pre-mediation stage, the mediation process, to the reporting of mediation results. However, mediation remains procedural and has not been fully effective in achieving reconciliation. This condition is reflected in the low number of successful mediations, namely 12 cases in 2022, 7 cases in 2023, 3 cases in 2024, and 1 case from January to April 2025. Factors contributing to mediation failure include the strong desire of the parties to divorce, prolonged marital conflicts, lack of good faith, technical obstacles such as distance of domicile, and limited internet access in conducting online mediation. Limited time availability of mediators and socio- cultural factors within the community also influence the effectiveness of mediation, resulting in mediation often failing to produce a peaceful settlement agreement.